Micromanipulation: Transfer of Individual Micro‐ and Nanoparticles for High‐Precision 3D Analysis Using 360° Electron Tomography (Small Methods 1/2018). Issue 1 (15th January 2018) - Przybilla, Thomas; Zubiri, Benjamin Apeleo; Beltrán, Ana M.; Butz, Benjamin; Machoke, Albert G. F.; Inayat, Alexandra; Distaso, Monica; Peukert, Wolfgang; Schwieger, Wilhelm; Spiecker, Erdmann
Abstract : In article number1700276, Erdmann Spiecker and co‐workers present a versatile approach that provides a general routine for the extensive and advanced 3D characterization of micro‐ and nanoparticles. The method, involving the transfer of individual particles onto tailored tips using a conventional scanning electron microscope equipped with a micromanipulator, enables damage‐ and contamination‐free preparation of freestanding particles and is demonstrated for 360° electron tomography of micro‐/macroporous zeolite micrometer‐sized particles and mesoporous alpha‐hematite nanoparticles.